2012
DOI: 10.1158/1055-9965.epi-12-0190-t
|View full text |Cite
|
Sign up to set email alerts
|

The MTAP-CDKN2A Locus Confers Susceptibility to a Naturally Occurring Canine Cancer

Abstract: Background Advantages offered by canine population substructure, combined with clinical presentations similar to human disorders, makes the dog an attractive system for studies of cancer genetics. Cancers that have been difficult to study in human families or populations are of particular interest. Histiocytic sarcoma is a rare and poorly understood neoplasm in humans that occurs in 15–25% of Bernese Mountain Dogs (BMD). Methods Genomic DNA was collected from affected and unaffected BMD in North America (NA)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
85
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(106 citation statements)
references
References 48 publications
(45 reference statements)
17
85
0
1
Order By: Relevance
“…Specially, recurrent deletions were detected in commonly described human tumour suppressor genes, including CDKN2A/B, RB1 and PTEN [86]. Interestingly, the GWAS of canine HS in BMDs (see above) localized a possible HS-risk allele also to CDKN2A (in addition to MTAP) [38]. Hedan et al [86] also identified several private CNAs unique and recurrent to each breed, perhaps suggesting a difference in initiation and/or progression leading to a more universal HS genomic phenotype once the tumour develops.…”
Section: (Iii) Histiocytic Sarcomamentioning
confidence: 99%
See 1 more Smart Citation
“…Specially, recurrent deletions were detected in commonly described human tumour suppressor genes, including CDKN2A/B, RB1 and PTEN [86]. Interestingly, the GWAS of canine HS in BMDs (see above) localized a possible HS-risk allele also to CDKN2A (in addition to MTAP) [38]. Hedan et al [86] also identified several private CNAs unique and recurrent to each breed, perhaps suggesting a difference in initiation and/or progression leading to a more universal HS genomic phenotype once the tumour develops.…”
Section: (Iii) Histiocytic Sarcomamentioning
confidence: 99%
“…This exceedingly rare sarcoma in humans occurs frequently in a few breeds of dog, including BMD, flat-coated retriever, Rottweiler and golden retriever. The lifetime risk of developing a HS in BMDs is 15-25% [38,39]. The authors performed the first GWAS in 111 BMD cases and 117 BMD controls from North America, as well as a second GWAS in 125 BMD cases and 117 BMD controls from Europe.…”
Section: Germline and Cancer Riskmentioning
confidence: 99%
“…Breeding from within a selected population of dogs can, in a relative short period of time, give rise to a clear change in phenotype which leads to breed development [1,2] but may also cause an increase in the occurrence of inherited diseases [3][4][5][6][7] such as cancer [8][9][10][11][12]. Clear evidence exists for a breed-related predisposition to specific cancers, like histiocytic sarcomas in Bernese Mountain dogs [10,13] and Flatcoated retrievers, [11] anal sac carcinomas in the English Cocker Spaniel [12,14] and hemangiosarcomas in German Shepherd dogs [15].…”
Section: Introductionmentioning
confidence: 99%
“…Elaine has also used her powerful genome-wide strategies to uncover polymorphisms involved in a variety of canine cancers. Because a poorly understood sarcoma that is rare in humans is quite common in Bernese mountain dogs, her group was able to find a haplotype common to the vast majority of affected animals, thereby pinpointing defective regulation of genes that had been implicated in human cancer (Shearin et al 2012). Elaine has articulated persuasively how the high resemblance of some canine and human diseases, the knowledge gained from veterinary medicine, and the ability to identify the genes underlying breed-associated diseases make dogs such a compelling model for human medical genetics (Ostrander 2012a).…”
Section: Challenging Cancer Geneticsmentioning
confidence: 99%